Low-dose (0.01%) atropine eye-drops to reduce progression of myopia in children: a multicentre placebo-controlled randomised trial in the UK (CHAMP-UK)—study protocol. Issue 7 (25th October 2019) - Azuara-Blanco, Augusto; Logan, Nicola; Strang, Niall; Saunders, Kathryn; Allen, Peter M; Weir, Ruth; Doherty, Paul; Adams, Catherine; Gardner, Evie; Hogg, Ruth; McFarland, Margaret; Preston, Jennifer; et al.
Abstract : Background/aims: To report the protocol of a trial designed to evaluate the efficacy, safety and mechanism of action of low-dose atropine (0.01%) eye-drops for reducing progression of myopia in UK children. Methods: Multicentre, double-masked, superiority, placebo-controlled, randomised trial. We will enrol children aged 6–12 years with myopia of −0.50 dioptres or worse in both eyes. We will recruit 289 participants with an allocation ratio of 2:1 (193 atropine; 96 placebo) from five centres. Participants will instil one drop in each eye every day for 2 years and attend a research centre every 6 months. The vehicle and preservative will be the same in both study arms. The primary outcome is SER of both eyes measured by autorefractor under cycloplegia at 2 years (adjusted for baseline). Secondary outcomes include axial length, best corrected distance visual acuity, near visual acuity, reading speed, pupil diameter, accommodation, adverse event rates and allergic reactions, quality of life (EQ-5D-Y) and tolerability at 2 years. Mechanistic evaluations will include: peripheral axial length, peripheral retinal defocus, anterior chamber depth, iris colour, height and weight, activities questionnaire, ciliary body biometry and chorioretinal thickness. Endpoints from both eyes will be pooled in combined analysis using generalised estimating equations to allow for the correlation between eyes within participant. Three years after cessation of treatment, we will also evaluate refractive error and adverse events. Conclusions: The Childhood Atropine for Myopia Progression in the UK study will be the first randomised trial reporting outcomes of low-dose atropine eye-drops for children with myopia in a UK population. Trial registration number: ISRCTN99883695, NCT03690089 .